Paysages de l’hydroélectricité, tourisme et protection de la nature en haute montagne : le Valais suisse - Jean-François Rodriguez; Séraphin Hirtz (Projets de Paysage, 2014)
In this initial phase of the energy transition which has become a necessity for Europe and the rest of the world, Switzerland has decided to adopt a strategy for the development of renewable energy by improving and increasing its hydraulic capacity as a part of the energy roadmap for 2050. This involves increasing the height of dams and the construction of new hydroelectric plants using a new high-performance pump-impeller technology for hydro-electric generation. In this context, the companies which operate the hydro-electric resources are also taking ecological compensatory measures, sometimes in association with nature conservation organisations, and are encouraging new approaches to the landscape and tourism. This process of industrial development in high mountain areas is consistent with the close historical interrelations between the exploitation of the resource, tourism in high mountain areas, and the conservation of nature since the beginning of hydro-electric power generation. It associates the defining of new heritage values and new guidelines for the representation of landscapes associated with hydro-electric installations involving the companies exploiting the hydro-electric resource in consultation with nature conservation organisations. The Valais Canton in Switzerland, which owns some of the largest dams in the mountain regions of Southern Europe bears witness to the importance of these interrelations and of their evolution since the beginning of the 20th century.